Low-frequency versus high-frequency stimulation of the pedunculopontine nucleus area in Parkinson's disease: a randomised controlled trial. Issue 6 (2nd September 2014) - Nosko, D; Ferraye, M U; Fraix, V; Goetz, L; Chabardès, S; Pollak, P; Debû, B
Abstract : Objective: To compare the influence of low-frequency (10–25 Hz) versus higher (60–80 Hz) frequency stimulation of the pedunculopontine nucleus area (PPNa) on akinaesia, freezing of gait and daytime sleepiness. Method: We included nine patients with Parkinson's disease (PD) and severe gait disorders. In this double-blind randomised cross-over study, patients were assessed after 24 h of PPNa stimulation. Assessments included the motor part of the Unified Parkinson's Disease Rating Scale, the Epworth Sleepiness Scale and a behavioural gait assessment. Results: Compared with 60–80 Hz, 10–25 Hz PPNa stimulation led to decreased akinaesia, gait difficulties and daytime sleepiness in 7/9 patients. In one patient, these symptoms were aggravated under 10–25 Hz stimulation compared with 60–80 Hz. Conclusion: These results are in keeping with the benefits of chronic PPNa stimulation for gait and postural difficulties in patients with PD, and with regard to the influence of patients' clinical characteristics, differential neuronal loss in the PPNa and electrode location. We conclude that in patients with PPNa stimulation, low frequency provides a better outcome than high-frequency stimulation.